The Mediating Role of Relational Ethics in the Relationship Between Emotional Maturity and Marital Burnout with Divorce Tendency in Young Couples - Atashpour , Seyed Salar; Saadati, Nadereh (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to examine the mediating role of relational ethics in the relationship between emotional maturity and marital burnout with divorce tendency among young couples.Methods and Materials: This study employed a descriptive correlational design using structural equation modeling. The statistical population consisted of young married individuals residing in Isfahan, from whom 300 participants were selected through cluster sampling; 298 complete questionnaires were analyzed. Inclusion criteria included residency in Isfahan, marriage duration of less than five years, and willingness to participate. Data were collected using standardized instruments including the Emotional Maturity Scale (Singh & Bhargava), the Marital Burnout Questionnaire (Pines), the Relational Ethics Scale (Hargrave et al.), and the Divorce Tendency Scale (Roselet et al.). Data were analyzed at descriptive and inferential levels using SPSS and AMOS software. Pearson correlation coefficients were calculated, and structural equation modeling was applied.Findings: Structural equation modeling demonstrated acceptable model fit. Emotional maturity had a significant negative direct effect on divorce tendency. Marital burnout had a significant positive direct effect on divorce tendency. Relational ethics had a significant negative direct effect on divorce tendency. The direct path from emotional maturity to relational ethics was not significant, and the indirect effect of emotional maturity on divorce tendency through relational ethics was also non-significant, indicating no mediation. In contrast, marital burnout had a significant negative effect on relational ethics, and its indirect effect on divorce tendency through relational ethics was significant, indicating partial mediation. The total effect of marital burnout on divorce tendency was positive and significant.Conclusion: Emotional maturity and relational ethics function as protective factors against divorce tendency, whereas marital burnout increases divorce proneness among young couples. Relational ethics partially mediates the association between marital burnout and divorce tendency but does not mediate the relationship between emotional maturity and divorce tendency.